Regulation of assisted reproduction under the European Union tissues and cells directives - Mocanu, Edgar (Henry Stewart Talks, 2015)
Regulation objectives, The directives, 2004/23/EC: standards of quality and safety, 2006/17/EC: technical requirements for the donation, procurement and testing of human tissues and cells, 2006/86/EC: traceability, notification of serious adverse reactions and events & technical requirements